THE IMPACT OF CRITICAL COMPETITIONS AND SUCCESS FACTOR IMPACT ON ALLIANCES PERFORMANCE IN THE MALAYSIAN COMPANIES - Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
Globalization has denationalized economic, markets, social and political environment today. Under the fierce competitive environment, Malaysian companies are also taking to new strategies and there is some evidence that they are forging strategic alliances either with local or foreign partners in search of their competitive advantage in this new economy. Thus the prime goals of this study to investigate the impact of resources on the various types of strategic alliances that are adopted by Malaysian companies. The empirical investigation is based on a survey on Malaysian firms in various industries. The survey questions contain the variables of resources, type of alliance, coopetition, critical success factors and alliance performance. Two types of test have been applied in this study. Pearson correlation applied is to explore the information of the relationship between any two variables. 2. The test of multivariate analysis of variance (MANOVA) and partial correlation was applied to rectify the hypothesis of this research. More studies are needed in order to discover the choice of strategic partners, the nature of coopetition that can facilitate the alliance to gain competencies, and the extent of key success factors that connects strategic alliance and resources. For instance, empirical information covering both qualitative and quantitative data would shed more light on these complex relationships and its underlying structure. Another area of interest is on the ways that firms select joint venture, equity alliance or functional alliance to optimize the resources in order to improve the performance.